On One Class of the Infinite Non-Abelian Groups - Tomanek, Ludovit; Tomankova, Anna (Communications - Scientific letters of the University of Zilina, 2010)
We present some properties of one class of the infinite non-abelian groups. We deal with a generalization of the INH and KI groups. Our main results are Theorem 1, 2, 3 and Theorem 4.